Emotional intelligence and coaching behavior of sport coaches in the state universities and colleges in region III, philippines - Dave, A.; Farin, E. N.; Farin, A. N. (International Journal of Sports Science, 2017)
This is a descriptive and correlational study that examined the relationship between emotional intelligence and coaching behavior of the sport coaches in the state universities and colleges in Region III. A total of 662 respondents, 165 coaches and 497 athletes were the respondents of the study. The study describes the perception of the respondents` emotional intelligence in terms of emotional awareness, managing emotions, self-motivation, empathy, and coaching others` emotions. The sport coaches and athletes indicate that the emotional intelligence of sports coaches was high. They were emotionally aware, can manage one`s emotion, self-motivated and empathetic. The coaching behavior of the sport coaches displayed during selection of athletes, during practices, before the game, during the game and after the game was described as very high positive. The coaching behavior of the sport coaches displayed during selection of athletes, during practices, before the game, during the game and after the game was perceived by the athlete-respondents to be high positive. The findings suggest that the sport coaches need to increase the level of their emotional awareness through emotional intelligence seminar-workshops. To maintain their very high positive coaching behavior, a continuing high quality coaching education program should be provided by the entire state universities and colleges in Region III.